Narrativas na perspectiva de: anúncio, denúncia e renúncia - Lima, Sebastião de Souza (2014)
This paper makes an outline of specific topics about the narratives presented in the contemporary means of communication on the segregation of the natural and human wealth in the state of Amazonas. The option was for a bibliographic investigation and research in registers which showed episodes described in the history of the inhabitants of this region. In the first chapter reference was made to the perspective of announcement with aspects of the colonized region, submitted to the orders of the Portuguese crown, which oppressed the colonized. The second chapter is described in the perspective of denouncement as it manifests indignation about the actions of social and economic segregation. The third chapter, in the perspective of renouncement, concentrated the essay on the criticism of the continuation of the actions directed by the contingent projects toward social and economic development. The research had its central focus on the analysis of the daily actions of segregation of the natural wealth and the exploitation of the work force in this locality. It elaborated a reflection about the distance between the occurrences in the past and the daily reality. The theoretical reference was based on authors who narrated unique episodes: Ferreira; Cunha, Piza, Ribeiro and Sousa who dealt with the Amazonian reality. One did not intend to exhaust this reflection, but one hopes that it may contribute to awaken the interest of others in social research with the perspective of suggesting public policies which contemplate the social well being of the less advantaged in the region.